LITERASI BUDAYA DI MUSEUM BALI BAGI PELAJAR SMP MELALUI PERLOMBAAN STORYTELLING “MEN BRAYUT” - Pradnya Dewi, Putu; Aliffiati, Aliffiati; Bagus Oka Wedasantara, Ida (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
This research aims to find out the development of cultural literacy at the Bali Museum for junior high school students in Denpasar City through a storytelling competition with the theme "Men Brayut". The methods of interview, observation, and literature study were used in this research. The data obtained in the field and literature sources that are in accordance with the problem are then described and interpreted qualitatively. The results of this study found that the implementation of the storytelling competition is one of the efforts of the Bali Museum manager which is quite significant in developing cultural literacy, especially for junior high school students in Denpasar City, through the assessment indicators set by the jury. The concept of the activity and the selection of themes are adjusted by telling the historical relics that are a collection at the Bali Museum, one of which is the relic of the statue "Men Brayut" in 2023.